Utilising dynamic simulation in design, development, and optimisation of a centrifugal-powered transmission apparatus. (2017) - Asiabanpour, Bahram; Fuentes, Jesus; Hawkes, Nicholas
The use of the centrifugal force and its wide range of applications in industry and end-user products have been recently investigated and reported. Additionally, different physical mechanisms using the centrifugal power transmission have been developed and tested. Owing to the high cost for developing such mechanisms, dynamic simulation has been used to study the design factors and to evaluate the optimised mechanism. This paper presents the results of an investigation that uses dynamic simulation to test the behaviour of a mechanism under an imposed motion or force for both two and four gears design models. Additionally, it illustrates the correlation between factors such as rotation speed and the generated torque in different design models. Product design, development, and test are presented as well.